Impact of contrasting tillage, residue mulch and nitrogen management on soil quality and system productivity under maize-wheat rotation in the north-western Indo-Gangetic Plains - Adak, Sujan; Bandyopadhyay, Kalikinkar; Purakayastha, Tapan Jyoti; Sen, Suman; Sahoo, Rabi Narayan; Shrivastava, Manoj; Krishnan, Prameela (Frontiers in Sustainable Food Systems, 2023)
The sustainability of dominant rice-wheat rotation is under threat due to numerous water-, nutrients-, weeds- and environment-related problems, mainly, due to rice cultivation in north-western Indo-Gangetic Plains (NWIGP) of India. It needs crop- and soil- appropriate management techniques with a focus on conservation agriculture (CA) that can maintain soil health which in turn is essential for long-term sustainability of intensive cereal-based systems. Thus, rice-wheat rotation may be diversified with maize as feasible substitute for rice. But, there is a dearth of comprehensive investigation on the impact of short-term CA in maize-wheat rotation, on soil quality. Hence, an attempt has been made to assess the system productivity (SP) and soil quality in a four-year-old CA-based maize-wheat rotation. Contrasting tillage as the main plot [Conventional tillage (CT), No–tillage (NT)], crop residue mulch as subplot [residue mulch (M+), no residue (M0)], and nitrogen [50 (N1), 100 (N2), 150% (N3) of recommended nitrogen dose] as sub-sub plot was laid out in split-split plot design. Soils sampled from 0–0.05, 0.05– 0.15, and 0.15–0.30 m soil layers were examined to develop a unified soil quality index (SQI) through principal component analysis (PCA) and expert opinion. The available K, P, total organic carbon (TOC), EC, bulk density (BD), dehydrogenase activity (DHA), and soil microbial biomass C (SMBC) were identified as the crucial minimum data set for SQI using PCA. Results showed that, NT and M+ plots had 10.52 and 17.39% higher mean weight diameter (MWD) than CT and M0, respectively at 0–0.05 m soil depth. NT and M+ plots increased TOC by 5.26 and 8% than CT and M0 plots, respectively in 0–0.05 m soil layer. Available K and P were found to be significantly higher in M+ plots than that of M0. NTM+ treatments improved SMBC and DHA than CTM0 treatments. The highest and lowest SQI was registered with NTM + N3 and CTM0N1, respectively. SP was significantly and positively correlated with SQI. Diversification of rice-wheat system with maize-wheat rotation following CA practices appears to have a positive impact on soil health. Therefore, CA-based maize-wheat rotation may be recommended to improve soil quality and system productivity in NWIGP region.